Export Diversification and Business Startups in Africa - Mazorodze, Brian Tavonga (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study examines the impact of export diversification on new business formation. Design/methodology/approach: Using an instrumental variable approach within a count data framework that relies on a panel dataset of 10 African countries (Algeria, Gabon, Lesotho, Morocco, Nigeria, Sierra Leone, Togo, Tunisia, Uganda and Zambia) observed between 2008 and 2018 annually, the evidence shows a non-trivial effect of export diversification on business start-ups. In particular, the odds of a new business being registered increase by 1.7 – 3.5 times in response to a percentage point increase in export diversification. Findings: This result reinforces the need for supportive policies aimed at moving away from concentrated export baskets towards more diversified ones to leverage entrepreneurial effort in the selected African countries. Paper type: Research Paper